ANALYSIS OF TEACHER COMPETENCY STANDARDS IN CREATING EFFECTIVE LEARNING AT SMP ALHILAAL KAMAL - Markus Marthen Somae; Izaak Hendrik Wenno; Paul Arjanto (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of teacher competency standards in creating effective learning at SMP Alhilaal Kamal, Kairatu Barat District, Seram Bagian Barat Regency. The research used a qualitative survey approach. Data were collected through interviews, observation, and documentation involving the principal, vice principal for curriculum, and teachers. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the implementation of teacher competencies has not been optimal. Pedagogical competence was reflected in teachers' awareness of classroom management, student characteristics, lesson planning, and learning evaluation, but learning devices and classroom practices were not consistently prepared and implemented. Professional competence was indicated by teachers' efforts to master subject matter and learning strategies, although preparation, media use, and self-development still needed improvement. Personality competence was reflected in expectations that teachers should be disciplined, responsible, mature, and exemplary, yet consistency in classroom control and student guidance remained weak. Social competence appeared in communication with students, colleagues, and parents, but collaboration among teachers and parental involvement were still limited. The inhibiting factors included limited teacher knowledge, motivation, commitment, experience, cooperation, facilities, and parental support. Supporting factors included school leadership, teacher willingness to improve, and the availability of basic learning facilities. The study concludes that effective learning requires continuous principal supervision, planned teacher competency development, stronger collaboration, and systematic evaluation of teacher performance.